2021
DOI: 10.1016/j.artd.2020.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sensory Deficit After Total Knee Arthroplasty on Patient Satisfaction and Kneeling Ability

Abstract: Background Skin numbness after total knee arthroplasty is a common complication. The incidence in the literature is variable from 27% to 100%. However, there is conflicting evidence about the consequences of this complication. The purpose of this study was to evaluate if postoperative numbness influenced patient satisfaction or kneeling ability. Methods We recruited patients who underwent a total knee arthroplasty for osteoarthritis one to 5 years before the study. Sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(36 reference statements)
0
5
1
Order By: Relevance
“…These findings contrast with previous evidence suggesting that an anterolateral skin incision provided a smaller area of cutaneous dysesthesia and higher rates of kneeling ability [8, 10, 14] [11]. However, another study concluded that after three years of mean followup, residual numbness following TKA surgery is not a predisposing factor for low kneeling ability or subjective dissatisfaction [15].…”
Section: Discussioncontrasting
confidence: 74%
“…These findings contrast with previous evidence suggesting that an anterolateral skin incision provided a smaller area of cutaneous dysesthesia and higher rates of kneeling ability [8, 10, 14] [11]. However, another study concluded that after three years of mean followup, residual numbness following TKA surgery is not a predisposing factor for low kneeling ability or subjective dissatisfaction [15].…”
Section: Discussioncontrasting
confidence: 74%
“…With their eyes closed, patients were asked to indicate the area that they felt to be numb on the translucent paper. This patient-reported AON was recorded as a value in cm 2 . The change in the AON was calculated by subtracting the AON at 3 months postoperatively from the AON at 2 weeks postoperatively.…”
Section: Aonmentioning
confidence: 99%
“…Tanavalee et al reported the AON at 2 weeks after TKA to be as large as 51.7 cm 2 , which gradually reduced to 2.1 cm 2 by 1 year postoperatively 7 . Additional studies 5,6 have reported the maximum AON to be approximately 191 cm 2 to 219 cm 2 .…”
mentioning
confidence: 97%
See 2 more Smart Citations